Solvent selection in membrane preparation from polyethylene terephthalate plastic waste: computational and experimental study - Badrut Tamam Ibnu Ali; Nurul Widiastuti; Yuly Kusumawati; Atthar Luqman Ivansyah; Juhana Jaafar (Materials Research Express, 2022)
The selection of the solvent during the membrane preparation process significantly affects the characteristics of the resulting membrane. The large number of organic solvents available for dissolving polymers renders this experimental approach ineffective. A computational approach can select a solvent using the solvation energy value approach. In addition, no organic waste is generated from the computational approach, which is a distinct advantage. A computational approach using the DFT/B3LYP/def2-TZVP RIJCOSX method was used to optimize the structure of polyethylene terephthalate (PET). The PET for the experiment was obtained from the utilization of plastic bottle waste. In addition, a review of the thermodynamics, geometry, HOMO-LUMO orbitals, and vibrational frequencies was conducted to validate the PET molecule against the experimental results. A conductor-like polarizable continuum model was used to determine the best solvent for dissolving the PET plastic waste. The results demonstrated that the Fourier Transform Infra-Red and Fourier Transform Raman spectra obtained from computational calculations were not significantly different from the experimental results. Based on a thermodynamic approach, computationally the Gibbs free energy (−724.723), entropy (0.0428), and enthalpy (−724,723 Kjmol ^−1 ) values of the PET dimer molecule are not much different from the experimental values (−601, 0.042, and −488 Kjmol ^−1 ). The computational approach was successful in selecting solvents that can dissolve PET plastic bottle waste. Phenol solvent has the lowest solvation energy value (−101.879 Kjmol ^−1 ) and the highest binding energy (2.4 Kjmol ^−1 ) than other solvents. Computational and experimental results demonstrated that the phenol solvent was able to dissolve PET plastic bottle waste better than the other solvents.